Kelakuan sambungan sambat bersama bar pilin dan bar memanjang dalam dinding konkrit pratuang - Shaedon, Shuhaimi (2012)
The strength of connections in precast concrete structure elements is the main factor that plays an important role in the Industrialised Building System. Various types of connections have been developed by previous researchers to improve the existing connections in the market. This study was conducted to develop a new splice sleeve connector, using spiral and elongated bar, which can produce comparable bond strength with the tensile capacity of reinforced bars. In the first phase of the study, 52 specimens were tested under tensile loads until all specimens reached their ultimate failure state. Based on the study conducted, ES-65-4-200 specimens with bar embedment length of 200 mm, spiral inner diameter of 65 mm, four elongated bars of Y10 inside the spiral bar, and use of grout was selected. In phase 2, the selected splice sleeve connector was used in the precast concrete wall panel system. Then, the connector was tested under shear loads to study the connection’s performance. In this phase, three monolithic specimens, three specimens with Nisso Master Builders (NMB) connectors, and three specimens with the proposed connector were tested. The performance of connections under tensile and shear loads was evaluated based on the ultimate loading capacity, displacement, strain, stress and failure mode. The results show that the wall specimens using spiral and elongated bar connectors, ES-65-4-200 achieve satisfactory structural performance with the ultimate shear capacity 28 % higher than monolithic wall and NMB wall connection. These results indicate that the combination of spiral and elongated bar is able to improve the performance of the splice sleeve connections in precast concrete wall structures.